Music as a science of mankind in eighteenth-century Britain - Semi, Maria (Ashgate Pub., 2012)
Music as a Science of Mankind offers a philosophical and historical perspective on the intellectual representation of music in British eighteenth-century culture. A particularly rich field of investigation, developed between the seventeenth and eighteenth centuries, was the British philosophy of the mind and of human understanding which looked at music and found in its realm a way of understanding human experience. Maria Semi sheds light on how these reflections moved towards a Science of Music: the discipline that was later to be known as 'musicology'.